Fostering Innovation in the U.S. Court System Identifying High-Priority Technology and Other Needs for Improving Court Operations and Outcomes - Jackson, Brian A. (RAND Corporation, 2016)
Given the challenges posed to the U.S. courts sector, such as high caseloads and resource constraints, it is valuable to identify opportunities where changes in technology, policy, or practice could improve performance. In this report, RAND researchers, with the help of a practitioner Courts Advisory Panel, seek to map out an innovation agenda for the sector.